Antisense Transcription of the Neurospora Frequency Gene Is Rhythmically Regulated by CSP-1 Repressor but Dispensable for Clock Function. Issue 3 (June 2023) - Cemel, Ibrahim A.; Diernfellner, Axel C. R.; Brunner, Michael
The circadian clock of Neurospora crassa is based on a negative transcriptional/translational feedback loops. The frequency ( frq ) gene controls the morning-specific rhythmic transcription of a sense RNA encoding FRQ, the negative element of the core circadian feedback loop. In addition, a long noncoding antisense RNA, qrf, is rhythmically transcribed in an evening-specific manner. It has been reported that the qrf rhythm relies on transcriptional interference with frq transcription and that complete suppression of qrf transcription impairs the circadian clock. We show here that qrf transcription is dispensable for circadian clock function. Rather, the evening-specific transcriptional rhythm of qrf is mediated by the morning-specific repressor CSP-1. Since CSP-1 expression is induced by light and glucose, this suggests a rhythmic coordination of qrf transcription with metabolism. However, a possible physiological significance for the circadian clock remains unclear, as suitable assays are not available.